The geopolitical landscape and Russia’s position in multidimensional political space - Fartyshev, Arseniy Nikolaevich (Frontiers in Political Science, 2025)
Since 2022, the concept of unfriendly countries has emerged in the political discourse due to the publication of the corresponding list by the Russian government. Concurrently, the countries and regions included in this list possess a de facto distinct position in relation to Russia, exhibiting varied levels of engagement with Russia. Despite the longstanding conceptualization of states as either friendly or hostile in political science, dating back to the seminal works of Klingberg and Wolfers, contemporary discourse in the field continues to explore the development of novel methodologies for the identification of international coalitions. This article offers a novel interpretation of the scale of friendliness-hostility from the perspective of political geography. It presents an algorithm developed by the author to assess the degree of friendliness or hostility among geopolitical subjects. This algorithm is based on a set of data, including diplomatic status, level of integration, military exercises, sanctions regimes, visa policy, coherence of votes in the United Nation General Assembly, and image in the media. A comprehensive evaluation was conducted, encompassing a 5-year period from 1990 to 2024, to ascertain the political disposition of the surrounding subjects toward Russia. The study’s findings indicate that the emergence of the two “flanks of unfriendliness” from the west and east of Russia occurred in a gradual fashion throughout the post-Soviet period. Concurrently, there was a parallel strengthening of the consolidation of the intra-Eurasian space. However, this consolidation does not occur with a sufficient degree of symmetry and tension. The consolidation of the intra-Eurasian space is illustrated cartographically. The focus of this study is Siberia, which, due to the aforementioned changes, is now considered the geographical heart of Greater Eurasia. The conclusion summarizes the results, emphasizing the dynamism of the geopolitical situation and the need for further study of interactions in the sphere of international relations in precise and quantitative categories and measurements. It also outlines further research using the presented algorithm for identifying the degree of international friendliness-hostility.